DEVELOPMENT OF ZOOGEOGRAPHICAL RESEARCH IN UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
Analyzing the dynamics of your studies will allow you to disclose the essence of what you have to do. In this article, studies on the study of the animal world in the territory of Uzbekistan between 1900 and 2000 were analyzed.